Effect of high-intensity focused ultrasound ablation on endometriosis of the abdominal wall - Zhang, Xiaoying (Int J Clin Exp Pathol, 2018)
In this study, we aimed to explore the effect of high-intensity focused ultrasound (HIFU) ablation on endometriosis of the abdominal wall. A total of 25 patients with abdominal wall endometriosis were selected after HIFU treatment, and their demographic characteristics were retrospectively analyzed. The blood perfusion of focus before operation and the focus ablation during or after operation were evaluated using ultrasound contrast, and follow-up for 24 months. Thirty lesions were ablated in 25 patients. Intermittent pain disappeared 1 month after the operation, and patients’ pain score significantly decreased, while the shrink ratio of lesions significantly increased with prolonged follow-up time. No severe complications were noted. HIFU ablation of abdominal wall endometriosis is an effective and safe method, with obvious long-term effects, and showed a significant guiding effect on the treatment of abdominal wall adenomyosis in the clinical setting.